Glass material and optical fiber
By adding specific element groups to the glass material and controlling the concentration of metal elements, the problem of structural deformation and absorption increase in glass materials after adding elements in the prior art is solved, and high transmittance and low loss in wide wavelength regions are achieved Effect.
Patent Information
- Application Number
- CN202380048152.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2023-06-06
- Publication Date
- 2025-02-07
AI Technical Summary
When the concentration of added elements increases, existing glass materials and optical fibers are prone to problems such as increasing Rayleigh scattering, increasing impurity absorption and deformation of the glass structure, resulting in an increase in the absorption of the ultraviolet wavelength region and making it difficult to achieve high transmittance in the wide wavelength region.
By adding at least one element in the Group 13 element group composed of boron, aluminum, gallium and indium to the glass material, and controlling the concentration of alkali metal elements and alkaline earth metal elements, the valence of the Group 13 elements is made to the glass material, and the concentration of alkali metal elements and alkaline earth metal elements is controlled to make it more valuable than that of the Group 13 elements. Consistent, thereby inhibiting deformation and defects of the glass structure.
A glass material and optical fiber with high transmittance in a wide wavelength region are realized, which reduces transmission losses, suppresses the occurrence of glass defects and structural inhomogeneity.
Smart Images

Figure HDA0005196121560000011 
Figure HDA0005196121560000021 
Figure HDA0005196121560000022
Abstract
Description
Technical Field
[0001] The present disclosure relates to a glass material and an optical fiber. This application claims priority based on Japanese Application No. 2022-104474 filed on June 29, 2022, and all the contents described in the Japanese Application are incorporated herein by reference. Background Art
[0002] Patent Document 1 discloses an optical fiber including a core doped with germanium. Germanium can increase the refractive index of the core.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2013-218247 Summary of the invention
[0006] A glass material according to one embodiment of the present disclosure is a glass material including silica-based glass, and includes at least one element of the Group 13 element group consisting of boron, aluminum, gallium, and indium. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 It is a cross-sectional view showing an optical fiber according to an embodiment.
[0008] Figure 2 This is a graph showing the relationship between the concentration ratio of aluminum and sodium and the transmission loss.
[0009] Figure 3 This is a graph showing the relationship between the concentration ratio of aluminum and calcium and the transmission loss. DETAILED DESCRIPTION
[0010] [Technical Problems to be Solved by the Present Disclosure]
[0011] If the concentration of the added element (dopant) increases, the following problems may occur. That is, Rayleigh scattering caused by composition fluctuations increases. In addition, the probability of impurities that may be contained in the dopant increases, and absorption in the ultraviolet and visible light regions caused by impurities may occur. Furthermore, the probability of the added element deforming the network structure of the silica glass increases, thereby generating glass defects, and as a result, the absorption in the ultraviolet wavelength region may become larger. In this field, it is desired to have a glass material and an optical fiber with high transmittance in a wide wavelength region.
[0012] An object of the present disclosure is to provide a glass material and an optical fiber having high transmittance in a wide wavelength range.
[0013] [Effects of the present disclosure]
[0014] According to the present disclosure, it is possible to provide a glass material and an optical fiber having high transmittance in a wide wavelength range.
[0015] [Description of Embodiments of the Present Disclosure]
[0016] First, the embodiments of the present disclosure are listed for explanation. (1) A glass material according to one embodiment of the present disclosure is a glass material comprising silica-based glass, comprising at least one element of the Group 13 element group consisting of boron, aluminum, gallium, and indium. The refractive index of the elements of the Group 13 element group varies greatly with respect to the amount of addition, and therefore, in the glass material, the concentration of a dopant for varying the refractive index can be suppressed. Therefore, high transmittance can be achieved in a wide wavelength region.
[0017] (2) The glass material of (1) above contains at least one element of the alkali element group consisting of alkali metal elements and alkaline earth metal elements. If the concentration of the alkali metal element is x and the concentration of the alkaline earth metal element is y, then x+2y may be 0.1 times or more and 10 times or less of the concentration of the element of the 13th group element group. In this case, since the valence of the element of the 13th group element group is consistent with the valence of silicon due to the element of the 13th group element, deformation of the glass structure caused by the 13th group element can be suppressed. As a result, the generation of defects can be suppressed and the homogenization of the glass structure can be promoted. Therefore, higher transmittance can be achieved in a wide wavelength range.
[0018] (3) The glass material of (1) above contains at least one element of the alkali element group consisting of alkali metal elements and alkaline earth metal elements, and if the concentration of the alkali metal element is x and the concentration of the alkaline earth metal element is y, then x+2y may be 0.2 times or more and 5 times or less of the concentration of the element of the Group 13 element group. In this case, higher transmittance can be achieved in a wide wavelength range.
[0019] (4) The glass material of (1) above contains at least one element of the alkali element group consisting of alkali metal elements and alkaline earth metal elements, and if the concentration of the alkali metal element is x and the concentration of the alkaline earth metal element is y, then x+2y may be 0.8 times or more and 1.2 times or less of the concentration of the element of the Group 13 element group. In this case, particularly high transmittance can be achieved in a wide wavelength range.
[0020] (5) In the glass material of any one of (1) to (4), the relative refractive index difference based on the refractive index of pure silica glass may be 0.0% or more. When the glass material is used to form a core, excessive addition of down dopants to the cladding can be suppressed.
[0021] (6) The glass material according to any one of (1) to (5) above may contain 50% by mass or more of silica glass. In this case, adverse effects on optical properties can be suppressed.
[0022] (7) The glass material of any one of (1) to (6) above may also contain at least two elements of the Group 13 element group. In this case, it is possible to suppress the inclusion of a large amount of a specific element of the Group 13 element group. Therefore, it is possible to suppress a phase separation state in which a substance is separated into two components as the concentration increases.
[0023] (8) An optical fiber according to one embodiment of the present disclosure includes: a core including silica-based glass and at least one element selected from the group consisting of boron, aluminum, gallium, and indium; and a cladding including silica-based glass and surrounding the core. The refractive index of the elements of the group 13 elements changes greatly with respect to the amount of addition, and therefore, in the optical fiber, the concentration of the dopant for changing the refractive index can be suppressed. Therefore, high transmittance can be achieved in a wide wavelength region, and thus the loss in the transmission band can be reduced.
[0024] [Details of the embodiments of the present disclosure]
[0025] Specific examples of the glass material and optical fiber disclosed in the present invention are described below with reference to the accompanying drawings. It should be noted that the present invention is not limited to these examples, but is represented by the claims, and is intended to include all changes within the meaning and scope equivalent to the claims. In the description of the drawings, the same elements are marked with the same reference numerals, and repeated descriptions are omitted.
[0026] (Glass material)
[0027] The glass material involved in this embodiment is, for example, an optical glass material. More specifically, the glass material is, for example, an optical fiber glass material, which is used to form the core of the optical fiber. The glass material is composed of a silica-based glass containing silica glass as a main component. The glass material also contains other elements other than silicon (Si) and oxygen (O) constituting the silica glass.
[0028] The glass material contains at least one element of the Group 13 element group consisting of boron (B), aluminum (Al), gallium (Ga), and indium (In). The concentration of the element of the Group 13 element group, i.e., the Group 13 element, may be 10 ppm or more, 50 ppm or more, or 1000 ppm or more.
[0029] The glass material may contain at least two elements of the group 13 element group, or may contain three or more elements. When the glass material contains a plurality of group 13 elements, the concentration of each group 13 element required to achieve a desired refractive index can be reduced. Therefore, it is possible to suppress the state in which the compound of the group 13 element and the element present in the glass separates into two components as the concentration increases.
[0030] If such a phase separation state occurs, light absorption and scattering will occur at the phase interface, resulting in changes in optical properties. These phase states vary greatly depending on the cooling rate of the glass manufacturing process, such as a slight temperature difference of about 10°C. Therefore, the controllability of the optical properties is greatly deteriorated. Therefore, it is very important to suppress phase separation. In the glass material for optical fiber, if other material phases are produced during the fiberization process, the hardness in the glass becomes uneven, and as a result, the target fiber diameter and refractive index distribution cannot be achieved. Therefore, in order to suppress the reduction in the yield of optical fiber, it is also important to suppress the concentration of each Group 13 element.
[0031] In the glass material for optical fiber, if other material phases are generated during the fiberization process, the hardness in the glass becomes uneven, and as a result, the target fiber diameter and refractive index distribution cannot be achieved. Therefore, in order to suppress the reduction in the yield of optical fiber, it is also important to suppress the concentration of each Group 13 element.
[0032] If phase separation of the additives occurs due to the addition of multiple elements, the optical properties will be adversely affected as described above. Therefore, the proportion of silica glass as the main component can be 50% or more, 90% or more, 95% or more, 98% or more, or 99% or more by mass ratio. Here, mass ratio refers to mass fraction.
[0033] The relative refractive index difference Δ of the glass material based on the refractive index of pure silica glass (SiO2), i.e., silica glass, can be 0.0% or more, 0.2% or more, or 0.3% or more. When such a glass material is used to form a core, it is possible to suppress excessive addition of downward dopants such as fluorine (F) to the cladding. Therefore, it is possible to suppress the increase in transmission loss caused by an increase in the doping concentration.
[0034] All Group 13 elements are upward dopants and are added according to the refractive index of the target glass material. If a single element, that is, only one Group 13 element is added, in the case of aluminum, the mass ratio can be more than 10 ppm, more than 1000 ppm, or more than 10000 ppm. In the case of boron, the mass ratio can be more than 10 ppm, more than 300 ppm, or more than 3000 ppm. In the case of gallium and indium, the mass ratio can be more than 10 ppm, more than 50 ppm, or more than 100 ppm. The refractive index of Group 13 elements relative to the amount of addition varies greatly, so the concentration of dopants used to change the refractive index can be suppressed. Therefore, the generation of problems with the increase in the concentration of dopants can be suppressed. That is, Rayleigh scattering caused by composition fluctuations can be suppressed. In addition, the probability of impurities that may be contained in the dopant is reduced, and the occurrence of absorption in the ultraviolet and visible light regions caused by impurities can be suppressed. Furthermore, the added elements reduce the probability of deformation of the network structure of silica glass, thereby suppressing glass defects and, as a result, suppressing absorption in the ultraviolet wavelength region. Here, the mass ratio refers to the mass fraction.
[0035] The glass material may also contain at least one element of the alkali element group consisting of alkali metal elements and alkaline earth metal elements. Examples of the alkali metal elements include lithium (Li), sodium (Na), potassium (K), and rubidium (Rb). Examples of the alkaline earth metal elements include magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba).
[0036] The elements of the alkali element group have the effect of making the valence of the 13th group element added to the glass material consistent with the valence of silicon. By performing such valence matching, the deformation of the glass structure caused by the 13th group element can be suppressed. As a result, it is possible to expect the effects of suppressing the generation of defects and promoting the homogenization of the glass structure. Therefore, for the glass material, a wide wavelength range can be expected in optical glass applications, and a reduction in transmission loss can be expected in optical fiber applications.
[0037] If the total amount of alkali metal elements added (molar concentration) is set to x, and the total amount of alkaline earth metal elements added (molar concentration) is set to y, then x+2y can be more than 0.1 times and more than 10 times the concentration of the elements of the 13th group element group, or more than 0.2 times and less than 5 times, or more than 0.8 times and more than 1.2 times. The concentration of the elements of the alkali element group can be more than 10ppm, or more than 50ppm, or more than 1000ppm. The tetravalence of silicon can be compensated by the trivalence of the 13th group elements and the monovalence of the alkali metal elements. Therefore, the amount of alkali metal element ions added can also be more than the amount of alkaline earth metal element ions added.
[0038] The glass material may contain a halogen element. Examples of the halogen element include fluorine (F), chlorine (Cl), bromine (Br), and iodine (I).
[0039] The synthesis of glass materials is achieved by heating and diffusing the solid or gaseous elements to be added. In order to achieve the above-mentioned valence matching, the diffusion state of the elements of the alkali element group and the elements of the 13th group can also be the same. The diffusion rate varies depending on the element, and the diffusion coefficient of the elements of the alkali element group is larger than the diffusion coefficient of the elements of the 13th group. Therefore, at the temperature of the diffusion addition element, the diffusion addition of the element is carried out on the basis of calculation in a manner that the diffusion rate × time is roughly equal.
[0040] (optical fiber)
[0041] Figure 1 : is a cross-sectional view showing an optical fiber according to an embodiment. The optical fiber 1 according to the embodiment comprises: a core 10 extending along a central axis 1a; and a cladding 20 covering the core 10. The optical fiber 1 is formed using a glass material according to the embodiment. More specifically, the core 10 is formed using a glass material according to the embodiment. The cladding 20 is composed of a silica-based glass containing silica glass as a main component.
[0042] Table 1 shows the relationship between the concentration ratio and the transmission loss.
[0043] [Table 1]
[0044] [Al] / [Na] Transmission loss [dB / km] [AI] / [Ca] Transmission loss [dB / km] 0.01 0.155 0.02 0.16 0.1 0.153 0.2 0.156 0.2 0.151 0.4 0.155 0.8 0.1495 1.6 0.153 1 0.148 2 0.151 1.2 0.15 2.4 0.153 5 0.153 10 0.156 10 0.156 20 0.161 50 0.163 125 0.182
[0045] Figure 2 It is a graph showing the relationship between the concentration ratio of aluminum and sodium and the transmission loss. Figure 2 As shown in FIG. 1 , the transmission loss is the lowest when the concentration ratio [Al] / [Na] of aluminum and sodium is 1. As the concentration ratio [Al] / [Na] becomes lower than 1, the transmission loss increases. As the concentration ratio [Al] / [Na] becomes higher than 1, the transmission loss increases.
[0046] Figure 3 It is a graph showing the relationship between the concentration ratio of aluminum and calcium and the transmission loss. Figure 2 As shown, the transmission loss is the lowest when the concentration ratio [Al] / [Ca] of aluminum and calcium is 2. As the concentration ratio [Al] / [Ca] becomes lower than 2, the transmission loss increases. As the concentration ratio [Al] / [Ca] becomes higher than 2, the transmission loss increases.
[0047] The concentration of each element can be determined by measuring with an electron probe microanalyzer. The concentration is evaluated by analyzing the measurement results of the spectral intensity of the characteristic X-rays of each element. The concentration is determined based on a calibration curve of spectral intensity and concentration prepared using a plurality of standard samples with different concentrations. The measurement conditions are, for example, an acceleration voltage of 20 kV, a detection beam diameter of less than 1 μm, and a measurement interval of 100 nm.
[0048] As mentioned above, although embodiment was described, this disclosure is not necessarily limited to the said embodiment and modification, Various changes are possible within the range which does not deviate from the summary.
[0049] Description of Reference Numerals
[0050] 1. Fiber Optic
[0051] 1a Central axis
[0052] 10 Core
[0053] 20 cladding.
Claims
1. A glass material, It is a glass material containing silica-based glass. Contains at least one element of the Group 13 element group consisting of boron, aluminum, gallium, and indium.
2. The glass material according to claim 1, contains at least one element of the alkali element group consisting of alkali metal elements and alkaline earth metal elements, If the concentration of the alkali metal element is x and the concentration of the alkaline earth metal element is y, then x+2y is 0.1 times or more and 10 times or less the concentration of the element of the Group 13 element group.
3. The glass material according to claim 1, The glass material contains at least one element of the alkali element group consisting of alkali metal elements and alkaline earth metal elements, If the concentration of the alkali metal element is x and the concentration of the alkaline earth metal element is y, then x+2y is 0.2 times or more and 5 times or less the concentration of the element of the Group 13 element group.
4. The glass material according to claim 1, The glass material contains at least one element of the alkali element group consisting of alkali metal elements and alkaline earth metal elements, If the concentration of the alkali metal element is x and the concentration of the alkaline earth metal element is y, then x+2y is 0.8 times or more and 1.2 times or less the concentration of the element of the Group 13 element group.
5. The glass material according to any one of claims 1 to 4, The relative refractive index difference based on the refractive index of pure silica glass is 0.0% or more.
6. The glass material according to any one of claims 1 to 5, The glass material contains 50% by mass or more of silica glass.
7. The glass material according to any one of claims 1 to 6, The glass material contains at least two elements from the Group 13 element group.
8. An optical fiber having: a core comprising silica-based glass and at least one element selected from the group consisting of boron, aluminum, gallium, and indium; and A cladding, comprising silica-based glass, surrounds the core.
Citation Information
Patent Citations
Optical fiber
JP2013218247A
Method for sucking and removing spinal cord of large fish
JP2022104474A